Characterization of the virulence, agr typing and antimicrobial resistance profile of Staphylococcus aureus strains isolated from food handlers in Brazil - Pereira, Giovana do Nascimento; Rosa, Rafael da Silva; Dias, André Aparecido; Gonçalves, Diego Júnior Santos; Seribelli, Amanda Aparecida; Pinheiro-Hubinger, Luiza [UNESP]; Eller, Lizziane Kretli Winkelstroter; de Carvalho, Thais Batista; Pereira, Valeria Cataneli (Elsevier, 2022)
Staphylococcus aureus is one of the main pathogens associated with foodborne outbreaks in Brazil and food handlers can carry toxigenic and resistant S. aureus strains. The aims of this study were to verify the frequency of virulence genes, to identify the agr groups and to determine the antimicrobial resistance profile of S. aureus strains isolated from food handlers of pilot kitchens located in São Paulo, Brazil. A total of 74 strains of the Staphylococcus genus were detected and 50% were identified as of the species S. aureus. The enterotoxin genes detection, tst and luk-PV detection, agr typing, mecA detection, ccr complex detection and SCCmec typing were performed using PCR. The antimicrobial resistance testing was performed by the disk diffusion method. The enterotoxin genes were identified in 36 S. aureus, including sea (83.8%). The tst gene was detected in 18.92% of the strains and the luk-PV was detected in only one isolate. Agr typing classified 58.3% of the strains as type I. Seven (18.92%) strains were classified as MRSA and the ccr2 complex was detected in six of these isolates. The SCCmec typing characterized strains as type II, III, IV and V. Moreover, there were also a greater number of resistant strains to penicillin (83.78%) and clarithromycin (67.57%). In conclusion, the study revealed a significant prevalence of S. aureus, and the presence of different virulence genes and a worrying resistance profile in S. aureus strains isolated from food handlers in this country.
Keywords: Food handlers; Food poisoning; MRSA; Staphylococcus; Toxins